Functional outcomes following various reconstructive methods following various forms of maxillectomies- a tertiary centre experience - Shankar, Amritha Prabha; B. R., Keerthi; M. S., Ganesh (International Journal of Research in Medical Sciences, 2017)
Background: The maxilla is the pivotal structure of the midface, separating the oral, antral, and orbital cavities, and providing support to the globes, lower eyelids, cheeks, lips, and nose. In addition, the maxilla play a critical role in speech, swallowing, and mastication. To evaluate the functional outcomes following various reconstructive methods following various forms of maxillectomies Methods: Retrospective analysis of medical records of patients who underwent various forms of maxillectomies from January 2011 to December 2013. Postmaxillectomy defects were managed by either prosthesis or local flaps. Results: Forty patients had various forms of maxillectomies. Fifteen patients had Browns class 1 maxilectomy and all of these patients underwent reconstruction with Pectoralis major myocutaneous flap. Ten patients underwent class 2a maxillectomy and reconstruction with obturator and Split skin thickness grafting. Nine patients underwent class 3a-b resection and four patients class 4a-b resection and all had reconstruction with temporalis myofascial flap. Two patients underwent orbitomaxillary resection with palate preserved and reconstruction with temporalis myofascial and forehead flap. Mean follow up period was 8 months (Range 6- 24 months). Two patients developed moderate grade of trismus after completion of radiotherapy. One patient developed recurrence in neck after 6 months of completion of adjuvant radiotherapy. All had moderate to fair speech and eating function which improved over time. Conclusions: There was no difference between flap reconstruction or obturator intervention of maxillary defects in speech and eating function. Small and lateral defects are better reconstructed with obturator and defects involving orbit and total maxilla are better reconstructed with regional flaps. Hence even in the era of microvascular flaps, obturator and regional flaps can still be considered for reconstruction of maxillectomy defects with fairly good outcome.